Methodological introduction to the carbon footprint evaluation of intermodal transport - Bielenia, Małgorzata; Dubisz, Damian; Czermański, Ernest (Frontiers in Environmental Science, 2023)
Managing logistics processes from an environmental perspective is increasingly important in international supply chains. Essential elements of global logistics are supply chains based on intermodal logistic units. The specificity of this type of shipment, which often involves several modes of transport, requires a precise definition of model boundaries and identification of specific factors determining the level of carbon footprint. This research is focused on identifying the specific emissivity level of each intermodal transport stage. The conducted study refers to the international emission evaluation guidelines gathered in the UN GHG Protocol. The carbon footprint (CF) evaluation commenced during the case study indicated the need to consider the specificity of the assigned modes of transport. Hence selected emission factors such as US DEFRA, US EPA, KOBiZE and UNFCCC were engaged for better CF evaluation related to each stage of the intermodal transport process. In the summary part, the environmental efficiency level of each mode of transport has been compared. The sea freight mode was indicated as the most efficient in terms of overall kg*eCO2 per kilometre. The study shows that intermodal maritime transport, taking into account the weight of the goods transported and the distance, is approximately 68% more efficient than road transport. However, it must be mentioned that to identify the differences comprehensively, transshipment operations must also be taken into account in each scenario. Further research steps and recommendations have been presented in the last section of this research.